Development and Current Status of Clinical Pharmacy Education in China - Hu, Ming (Am J Pharm Educ, 2014)
Objective. To describe the current status and developing trend of clinical pharmacy education in China. Methods. Descriptive analysis of data and information about the clinical pharmacy specialty, pharmacy colleges, and curriculum from literature, college websites, and statistics from the Ministry of Health (MOH) and Ministry of Education (MOE) websites was conducted. Results. Clinical pharmacy programs were established in China in 1989 but developed more fully after 2006. In 2012, there were 30 pharmacy colleges with clinical pharmacy undergraduate programs, which included a bachelor’s degree in clinical pharmacy and a clinical pharmacy concentration within the BS programs of pharmacy or medicine. More than 40 colleges within the university system offer 4 types of master’s degree programs in clinical pharmacy. Five universities offer a PhD program in clinical pharmacy. Three postgraduate programs exist, which train hospital pharmacists and clinical pharmacists: the 3+2 year Hospital Pharmacist Standardized Training Program at Peking hospitals; the 1-year Clinical Pharmacist Training Program sponsored by the MOH; and the 2-year Clinical Pharmacist Residency Program provided by West China Hospital at Sichuan University. Conclusion. A growing clinical pharmacy education system has been established and has become an important subfield in Chinese pharmacy education. Measures should be taken to further promote the development of clinical pharmacy education in China.